Simulation of shunt capacitor switching transient - Ismael Husein Almabrouk (School of Electrical System Engineering, University Malaysia Perlis, 2014)
In this work we used the numerical method applied by ATP software to investigate the transient effect on the quality and quantity of system. Investigations for the cases of Energization inrush, Back to back switching, Outrush Transient, Voltage Magnification and Transient Recovery Voltages was done.